دراسة النمو وزيادة الوزن الحي عند الماعز الجبلي - حبيب فؤاد (Latakia University Journal -Biological Sciences Series, 2019)
يهدف البحث إلى التعرف على خصائص النمو عند مواليد الماعز الجبلي الأسود تحت النظام شبه المكثف ، لدى أحد المربيين في المرتفعات الجبلية الساحلية التابعة لمحافظة اللاذقية من القطر العربي السوري. وتم تسجيل الأوزان الحية لـ (35) مولوداً لعام (1996) و(42) مولوداً لعام (1997) و(51) مولوداً لعام 1998 من الميلاد وحتى عمر (6) أشهر . وقد خلص البحث إلى النتائج التالية: - تبين من خلال القياسات الشهرية الدورية أن أوزان المواليد تأثرت بجنس المولود ، ونوع الولادة ، وطريقة الفطام المتبعة . - أوضحـت النتائج أن أوزان مواليد الماعز الجبلي تصل كحد متوسط إلى (2.87) كيلو غراما عند الميلاد، و( 9.74) كيلو غراما عند الفطام بعمر (60) يوماً . و(23.570 ) كيلو غراما بعمر (6) أشهر . - وإذا أخذنا الولادات المتعدد بعين الاعتبار فإن المعزاية تعطي أكثر من (5.610) كغ من المواليد عند الميلاد يزيد وزنها بعمر الفطام عن (18.50) كغ. ولقد تأثرت أوزان المواليد بجنس المولود ونوع الولادة وطريقة الفطام . - بلغت سرعة الزيادة اليومية في الوزن الحي للمواليد (100.66 – 132 ) غ خلال مرحلة الرضاعة . ومن الفطام وحتى عمر (6) أشهر وعلى التوالي ( 67 - 112.33 – 175.32 – 102.30 ) غ يومياً . - كان لجنس المولود ونوع الولادة والمقدرة الإنتاجية للأم تأثير على سرعة الزيادة اليومية في الوزن الحي للمواليد في مرحلة الرضاعة التي لا تطول عن (60) يوماً على الأكثر . وفي مرحلة ما بعد الرضاعة يتلاشى تأثير هذه العوامل الثلاث تدريجياً مع تقدم المواليد في العمر . - إن الحد المتوسط للزيادة اليومية في الوزن الحي للمواليد كان متقارباً في مرحلة الرضاعة وما بعد هذه المرحلة وعلى التوالي (116.33 – 114.25 ) غ يومياً ، وشبه متساوية بالنسبة للمواليد الناتجة عن الولادات المتعددة (117.83 – 117.33 ) غ يومياً . - لقد تبين من خلال الدراسة أن تباطؤ سرعة النمو عند مواليد الولادات المتعددة في مرحلة الرضاعة ، بغض النظر عن الجنس ، يعوض بسرعة في المرحلة الثانية مابعد الرضاعة بوقت قصير وقبل البلوغ، لذى لا خوف على العملية الإنتاجية من التأخير بسبب زيادة نسبة عدد الولادات التوأمية . The objectives of this investigation were to identify growth characteristics of newborn black mountain goats under the semi-expanded system. The study was conducted in the coastal mountains of Lattakia (Syrian Arab Republic) at the farms of the best-known livestock growers. Weights and growth rates of 35 newborn goats were recorded during 1996 and 42 newborn goats in 1997 and 51 newborn goats in 1998. The weights and growth rates were recorded from birth to an age of 6 months. The periodical monthly measurements showed that sex, the birth method, and the weaning method affected newborn weights. The average weight of newborn goats was 2.87 kg at birth, 9.74 kg at weaning time at an age of 60 days and 23.57 kg at an age of 6-month. If we consider the multi-birth, the female goat gives more than 5.61 kg of newborns that will weigh more than 18.5 kg at weaning time. Sex of newborns, the birth method, and the weaning method influenced the weights. The average daily gain in biomass was 100.66 – 132.00 grams during the suckling period, 67.00- 112.33 grams at weaning time, and 175.32-102.30 grams at and age of 6-month. Sex, birth method, and productive capacity of the mother influenced the rate of daily weight gain of newborns during the suckling period, which did not exceed 60 days. The influence of these factors was diminished gradually after weaning as age progresses. The average daily gain of newborns was almost the same during the breast-feeding and after suckling periods, and was 116.33 and 114.25 grams, respectively. The average daily gain during the two period was also similar for multi-births and was 117.83 and 117.33 grams, respectively. The slow rate of growth during the following period in a relatively short period and before maturity. Therefore, the multi-births do not negatively affect productivity.